Optimalisasi Pembenihan Ikan Nila dengan Puddle System pada Kelompok KJA Mina Makmur Jaya Malang - Muhammad Musa; Mohammad Mahmudi; Aminudin Afandhi; Dwi Ayu Lusia; Evellin Dewi Lusiana; Mawadah Ikah Hamidah; Dani Anggraini; Anugrah Fakhri Fadhlullah Mahmuda; Vella Ananda Sari; Riski Pebri Sandikah (Abdi Geomedisains, 2025)
The Mina Makmur Jaya Floating Net Cage (KJA) Group in Gampingan is a community group engaged in the breeding of Nile tilapia (Oreochromis niloticus) using the puddle system method, located in Gampingan Village, Pagak District, Malang Regency. The main problem faced in this business is the slow growth of fish fry, which results in suboptimal seed production. This condition is caused by several factors: water quality that is highly dependent on weather conditions, inappropriate breeding techniques, and inadequate nutrition or feed. The proposed solutions include conducting socialization activities and preparing a water quality management module based on Adaptive Water Management, providing water quality measuring instruments, organizing training and SOP development for seed breeding and packaging techniques, and conducting socialization on feed management for tilapia hatchery. The results of these activities showed an increase in partners’ technical skills, business management efficiency, and seed quality. In addition, outputs were produced in the form of SOPs, training modules, activity documentation, and new skills that help improve tilapia fry productivity, reduce operational costs, and expand distribution reach. Thus, this program contributes to strengthening food security, increasing economic value, and ensuring the sustainability of tilapia breeding enterprises at the local level.